Practical strategies to achieve resilient health systems: results from a scoping review - David Bishai; Basma M. Saleh; Maryam Huda; Eman Mohammed Aly; Marwa Hafiz; Ali Ardalan; Awad Mataria (BMC, 2024)
Abstract Background This paper presents the results of a systematic review to identify practical strategies to create the institutions, skills, values, and norms that will improve health systems resilience. Methods A PRISMA 2020 compliant systematic review identified peer-reviewed and gray literature on practical strategies to make health systems more resilient. Investigators screened 970 papers to identify 65 English language papers published since 2015. Results Practical strategies focus efforts on system changes to improve a health system's resilience components of collective knowing, collective thinking, and collaborative doing. The most helpful studies identified potential lead organizations to serve as the stewards of resilience improvement, and these were commonly in national and local departments of public health. Papers on practical strategies suggested possible measurement tools to benchmark resilience components in efforts to focus on performance improvement and ways to sustain their use. Essential Public Health Function (EPHF) measurement and improvement tools are well-aligned to the resilience agenda. The field of health systems resilience lacks empirical trials linking resilience improvement interventions to outcomes. Conclusions The rigorous assessment of practical strategies to improve resilience based on cycles of measurement should be a high priority.